KEBIJAKAN EGO SEKTORAL DAN RENDAHNYA IMPLEMENTASI HUKUM SEBAGAI PEMICU KONFLIK TANAH HAK ULAYAT - Sukirno Sukirno (Masalah-Masalah Hukum, 2010)
Recognize of the existence of traditional law society and their right including communal land is acknowledged, distributed in various regulations and laws. However, the existence of this regulation does not give much meanings because it is still underestimated by the regional government, proven that there are still many territorial right land conflicts. This research is conducted to findout solutions for the problems relating to the rearangement of territorial of communal right land with the purpose of being able to find out and formulate the appropriate arangement model both from the aspect of format and legal formulation. The research results conclude: firstly, horizontally and vertically, the are many laws and orders that are not synchronous, harmonious, overiaping to each other, and they prone to couse conflicts, especially the matters concerning the communal land. Secondly, the regulations that will be created would be better if they have an equal level to Acts as mandated in the Second Amendment of 1945 Constitution. Thirdly, the formulation that should exist in that Act should at least include: 1) acknowledgment of traditional law society with their communal right land from the government; 2) utilization of FPIC (Free, Prior and Informed Concent) instruments reflected in UNDRIP (United Nations Declaration on the Right of Indigenous Peoples) as the conditions of communal right land usage by outside parties; 3) measurement, communal right land mapping, and construction of pole s borders; 4) issuence of proprietary right certificatea or usage right upon the communal right land by paying attention to the characteristics of the traditional law society